A corrosion model for CZ cladding based on in-pile irradiation data - Duoting, Xu; Xiaoyan, Wei; Xiaohan, Liu; Xin, Jin; Tao, Wang (Frontiers in Energy Research, 2024)
Corrosion resistance is the critical in-pile property for developing new zircaloy cladding. As a new zircaloy developed by China General Nuclear Power Corporation, CZ will be used as fuel rod cladding. This study is devoted to investigating the corrosion behavior of CZ. A two-stage Arrhenius equation is proposed to model the corrosion rate. 1510 measurement data taken from 151 fuel rods irradiated for 1 to 4 cycles are used to develop the corrosion model. The burnup of these fuel rods ranges from 13.7 MWd/kgU to 55.9 MWd/kgU. The mean value and standard deviation of P-M (predicted value minus measure value) are respectively 0.54 micron and 3.65 microns, and the mean value and standard deviation of P/M (predicted value divided by measure value) are respectively 1.09 and 0.34. Generally, P-M and P/M increase with the local burnup. When the burnup is larger than 40 MWd/kgU, the mean value of P-M and P/M are respectively 6.2 microns and 1.20 while the prediction of the proposed model is more conservative in high burnup. In the typical case of which the average burnup reaches 57 MWd/kgU, the oxide thickness of CZ cladding is much less than 30 microns. Whereas the oxide thickness of Zr-4 cladding is about 80 microns and this manifest that CZ cladding possesses excellent performance in corrosion resistance.